The Effect of Supplementation Sunflowers (Helianthus annuus L.) and BIOPLUS to the Solid Non Fat, Total Solid and Milk Acidity of Sub-clinical Mastitisâs Holstein Dairy Cows - Nurdin, E (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2007)
A research about âThe Effect of Supplementation Sunflowers (Helianthus annuus L.) and BIOPLUS to the Solid Non Fat, Total Solid and Milk Acidity of Sub-clinic Mastitisâs Holstein Dairy Cowsâ had been done in a small farm at Nagrak Kulon Valley, Lembang-Bandung. The aim of this research is to know about the effect of supplementation Sunflower and BIOPLUS to the Solid Non Fat (SNF), Total Solid (TS) and Milk Acidity (pH) of sub-clinic Mastitisâs Holstein Dairy Cows.Â This research using 16 Holstein Dairy Cows with 2-4 lactation periode and 2-4 lactation month. The method that using in this research is Random groups method with 4 treatment such as R0 (control), R1 (0.01% body weight of sunflowers), R2 (100 gram of BIOPLUS) and R3 (R1 + R2).Â As the result of this research is no effect (P>0.05) of supplementation sunflowers and BIOPLUS to the Solid Non Fat, Total Solid and Milk Acidity of Sub-clinical Mastitisâs Holstein Dairy Cows. SNF is 8.50 % - 8.75 %, TS is 12.51 % - 12.65 % and pH is 6.72 â 6.85. (Animal Production 9(2): 79-81 (2007)Â Key Words : Sunflowers, BIOPLUS, Sub-clinical Mastitis, SNF, TS, pH